Dynamic analysis of SEIR model for Covid-19 spread in Medan - Sihaloho, Ruth Salisa; Nasution, Hamidah (Jambura Journal of Biomathematics (JJBM), 2022)
In this study, a mathematical model was studied on the population of the spread of Covid-19 in Medan which the model use an epidemic mathematical model, SEIR (Susceptible, Exposed, Infected, and Recovered). Next, we determine the basic reproduction number R0 using the next generation matrix and the equilibrium point which is analyzed using the Routh Hurwitz criteria. The disease-free equilibrium point is said to be locally asymptotically stable if R01 and the endemic equilibrium point is said to be locally asymptotically stable if R01. Numerical simulation of the model was carried out using real data on the number of Covid-19 cases in Medan and with the help of Maple software. Through the data obtained, the value of R01 indicates that Covid-19 at the time of the study was still contagious to other individuals. Furthermore, based on the simulation formed from the SEIR model with the given initial and parameters, it was found that the greater the contact rate or the transmission rate, the more spread the disease would be and the smaller the cure rate, the more the disease would spread.